2019
DOI: 10.3390/app10010241
|View full text |Cite
|
Sign up to set email alerts
|

Blast-Resistant Performance of Hybrid Fiber-Reinforced Concrete (HFRC) Panels Subjected to Contact Detonation

Abstract: This paper experimentally investigates the blast-resistant characteristics of hybrid fiber-reinforced concrete (HFRC) panels by contact detonation tests. The control specimen of plain concrete, polypropylene (PP), polyvinyl alcohol (PVA) and steel fiber-reinforced concrete were prepared and tested for characterization in contrast with PP-Steel HFRC and PVA-Steel HFRC. The sequent contact detonation tests were conducted with panel damage recorded and measured. Damaged HFRC panels were further comparatively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The fiber-hybrid effect index was introduced to evaluate the hybrid effect on the explosion-resistance performance of HFRC panels. It revealed that neither PP-fiber nor PVA-fiber provide a positive hybrid effect on blast-resistant improvement of HFRC panels [17].…”
Section: Introductionmentioning
confidence: 93%
“…The fiber-hybrid effect index was introduced to evaluate the hybrid effect on the explosion-resistance performance of HFRC panels. It revealed that neither PP-fiber nor PVA-fiber provide a positive hybrid effect on blast-resistant improvement of HFRC panels [17].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, alkali-aggregate interaction, carbonation, and loading can all cause significant damage to concrete, leading to a reduction in both its usability and durability. Accidents resulting from Table 3 -Raw material, mix proportion and increased strengths of HFRC [19,48,51,57,65,66].…”
Section: Durability Flaws In Concretementioning
confidence: 99%
“…According to the findings, natural Fig. 1 -Various hybrid fibers and single fiber used in cementitious materials: (a) Steel fiber and Carbon fiber [15]; (b) Basalt fiber and Polypropylene fiber [16]; (c) Jute fiber, Polyvinyl alcohol fiber and Nylon fiber [17]; (d) Jute fiber [18]; (e) Steel fiber, polypropylene and polyvinyl alcohol [19]; (f) Jute fiber [20]; (g) Jute fiber [21]; (h) Polypropylene fiber, Polyvinyl alcohol fiber and Steel fiber [22].…”
Section: Introductionmentioning
confidence: 99%
“…[9] chỉ ra rằng cốt sợi thép hiệu suất thấp (low-performance steel fiber) không ảnh hưởng đáng kể đến khả năng chống nổ của các tấm bê tông cốt sợi, trong khi đó dữ liệu thử nghiệm được thực hiện bởi Yao và cs. [27] cho thấy tấm FRC sợi thép cho khả năng chống tải trọng nổ tốt nhất so với các loại tấm sử dụng sợi hỗn hợp (là sự kết hợp giữa sợi thép, polypropylene và polyvinyl alcohol). Trong các thử nghiệm của Foglar và cs.…”
Section: ảNh Hưởng Của Hàm Lượng Cốt Sợiunclassified